Glucan particles loaded with a NIRF agent for imaging monocytes/macrophages recruitment in a mouse model of rheumatoid arthritis1. Issue 43 (14th May 2015) - Garello, Francesca; Arena, Francesca; Cutrin, Juan Carlos; Esposito, Giovanna; D'Angeli, Luca; Cesano, Federico; Filippi, Miriam; Figueiredo, Sara; Terreno, Enzo
<x xml:space="preserve">Abstract</x> We report here the in vivo recruitment of immune cells in inflamed sites on a mouse model of rheumatoid arthritis (CIA) by NIRF imaging of fluorescent glucan microspheres (GPs).